Effect of the integrated science, technology, and society (STS) learning approach with tecnological pedagogical content knowledge(TPACK)to cognitive learning outcomes and metacognitive abilities onState Vocational School West Seram - Netty Charla Kilay; Hasan Tuaputty; Alwi Smith (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
West Seram Regency is one of the areas that has quite low quality educationThere needs to be innovation in using several learning approaches. Learning approacheswhich can be used to solve problems in the surrounding environment and is technology-based, namely Science Technology and Society (STS) andTechnological Pedagogical Content Knowledge (TPACK).This research aims to determine the effectlearning approachesTPACK integrated STS on cognitive learning outcomes and metacognitive abilities on ecosystem material in Class X students of West Seram Vocational School. This type of research isquasi-experiment. The research population was State Vocational School 2 West Seram, State Vocational School 9 West Seram and West Seram State Vocational School 12 with a total sample of 33 students. The research instruments used were metacognitive ability tests and questionnaires and analyzed using Ancova. The research results show thatthere is an influence of the TPACK integrated STS learning approach on cognitive learning outcomes, there is an influence of the TPACK integrated STS learning approach on metacognitive abilities, and there is an influence of the TPACK integrated STS learning approach on cognitive learning outcomes and metacognitive abilities